Visual Multiplexing. (June 2014) - Chen, M.; Walton, S.; Berger, K.; Thiyagalingam, J.; Duffy, B.; Fang, H.; Holloway, C.; Trefethen, A. E.
Abstract The majority of display devices used in visualization are 2D displays. Inevitably, it is often necessary to overlay one piece of visual information on top of another, especially in applications such as multi‐field visualization and geo‐spatial information visualization. In this paper, we present a conceptual framework for studying the mechanisms for overlaying multiple pieces of visual information while allowing users to recover occluded information. We adopt the term 'multiplexing' from tele‐ and data communication to encompass all such overlapping mechanisms. We establish 10 categories of visual multiplexing mechanisms. We draw support evidence from both perception literature and existing works in visualization to support this conceptual framework. We examine the relationships between multiplexing and information theoretic measures. This new conceptual categorization provides the much‐needed theory of visualization with an integral component.